Headwater Streams of the Flint Hills - David Edds (Symphony in the Flint Hills, 2012)
Among the most beautiful environments of the Flint Hills are the springs and headwater streams that are part of and help to carve the landscape. Meandering through the vast sea of grass, hundreds of free-flowing ribbons of water might go unnoticed as we speed along the highway.
Keywords: Streams; rivers; map; flint hills; water; landscape; grassland; prairie; environment; spring-fed; spring water; headwater; fish; fishing; creek; wildlife; birds; invertebrate; plants; algae; ferns; Lyon County